2020
DOI: 10.3390/ijerph17155475
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Masculinity and Internalized Homophobia amongst Australian Gay Men

Abstract: Due to the heterosexist ideals associated with gender norms, gay men often experience negative attitudes towards their own sexuality—internalized homophobia. As a result, gay men often feel compelled to compensate for their perceived lack of masculinity. The study aimed to investigate the relationship and predictive power of masculinity on gay men’s experiences of internalized homophobia. A sample of 489 self-identified Australian gay men 18–72 years old participated in an online survey on masculinity and homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Furthermore, the stories shared by the gay men within this study depict anti-effeminacy and social-regulation of gender expression among other gay men within their micro and mesosystems, notably straight-acting gay men. It is suggested that gay men who conform more to masculine norms, as well as self-identify as straight-acting, possess higher degrees of internalized homonegativity [4,55]. Thepsourinthone, Dune, Liamputtong and Arora [4] argued that gay men high in internalized homonegativity are motivated to maintain a distinct gender identity from other gay men (in this case, femme gay men) through perceptions of masculinity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the stories shared by the gay men within this study depict anti-effeminacy and social-regulation of gender expression among other gay men within their micro and mesosystems, notably straight-acting gay men. It is suggested that gay men who conform more to masculine norms, as well as self-identify as straight-acting, possess higher degrees of internalized homonegativity [4,55]. Thepsourinthone, Dune, Liamputtong and Arora [4] argued that gay men high in internalized homonegativity are motivated to maintain a distinct gender identity from other gay men (in this case, femme gay men) through perceptions of masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is a part of a larger body of research exploring masculinity and internalized homonegativity amongst gay men. Limited research explicitly focuses on masculinity and internalized homonegativity [4,25,45,46] with very few using qualitative methods [22]. The study, therefore, aims to qualitatively explore this under-examined area, focusing on men's lived experiences of internalized homonegativity, the factors which contribute to their experiences, and the impact it may have on their health and wellbeing.…”
Section: Present Studymentioning
confidence: 99%
See 3 more Smart Citations